Helicobacter pylori infection is an independent risk factor for colonic adenomatous neoplasms - Nam, Ji Hyung; Hong, Chang Won; Kim, Byung Chang; Shin, Aesun; Ryu, Kum Hei; Park, Bum Joon; Kim, Bun; Sohn, Dae Kyung; Han, Kyung Su; Kim, Jeongseon; Lee, Chan Wha (Cancer causes & control, 2017)
Purpose Helicobacter pylori infection is considered to have a positive association with colorectal neoplasms. In this study, we evaluated the association between H. pylori infection and colorectal adenomas, based on the characteristics of these adenomas in Korea, where the prevalence of H. pylori infection is high and the incidence of colorectal cancer continues to increase. Methods The study cohort consisted of 4,466 subjects who underwent colonoscopy and esophagogastroduodenoscopy during screening (1,245 colorectal adenomas vs. 3,221 polyp-free controls). We compared the rate of H. pylori infection between patients with adenoma and polyp-free control cases, using multivariable logistic regression analysis. Results The overall rate of positive H. pylori infection was higher in adenoma cases than in polyp-free control cases (55.0 vs. 48.5%, p < 0.001). The odds ratio (OR) of positive H. pylori infection in patients with adenoma compared to polyp-free controls was 1.28 (95% CI 1.11–1.47). The positive association of H. pylori infection with colorectal adenomas was more prominent in advanced adenomas (OR 1.84, 95% CI 1.25–2.70) and multiple adenomas (OR 1.72, 95% CI 1.26–2.35). Based on the location of these adenomas, the OR was significant only in patients with colonic adenomas (OR 1.31, 95% CI 1.13–1.52) and not in those with rectal adenoma (OR 0.85, 95% CI 0.58–1.24). Conclusion Helicobacter pylori infection is an independent risk factor for colonic adenomas, especially in cases of advanced or multiple adenomas, but not for rectal adenomas.